Penyuluhan Kegawatdaruratan Dalam Kedokteran Gigi Serta Penanggulangannya Kepada Orang Tua Murid SD Yasporbi I Jakarta Selatan - Seftiana Indah Sari, Eka; Prijanti Dwisaptarini, Ade; Melaniwati; Pragustine, Yenny; Talenta Theresia, Tiarma (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Management of dental emergencies focuses on immediate action to relieve pain and preserve injured tissue so that the condition does not get worse. Some of the causes of dental emergencies include pain due to inflammation of the dental nerve, bacterial infections that cause abscesses or swelling, broken or loose teeth due to falls or impacts. Dental emergencies can also occur with dental tools installed in the oral cavity, such as dentures or orthodontic wires, for example broken dentures or sharp orthodontic wires that can cause injuries to the soft tissue in the oral cavity. This empowerment activity aims to improve knowledge and ability to handle oral emergencies. This Community Service Activity was carried out by the Trisakti University Faculty of Dentistry Team for parents of students at Yasporbi I Elementary School, South Jakarta on February 16 2024. The method used was offline counseling using presentations regarding various emergency conditions in dentistry. Counseling was conducted on 13 participants for 60 minutes. Participants' knowledge was assessed with a pre-test and posttest using Google Form. From the results obtained, it can be seen that there has been an increase in the knowledge of the counseling participants by 25% (average pre-test score 8 and average post-test score 10).